Single chain fragment variable, a new theranostic approach for cardiovascular diseases - Zahid, Rukhshan; Wang, Juncheng; Cai, Zecheng; Ishtiaq, Ayesha; Liu, Meng; Ma, Dan; Liang, Yan; Xu, Yuekang (Frontiers in Immunology, 2024)
Cardiovascular diseases (CVDs) remain a significant global health challenge, leading to substantial morbidity and mortality. Despite recent advancements in CVD management, pharmaceutical treatments often suffer from poor pharmacokinetics and high toxicity. With the rapid progress of modern molecular biology and immunology, however, single-chain fragment variable (scFv) molecule engineering has emerged as a promising theranostic tool to offer specificity and versatility in targeting CVD-related antigens. To represent the latest development on the potential of scFv in the context of CVDs, this review summarized the new mechanism of action and applications as therapeutic, as well as diagnostic agents. Furthermore, the advantages of scFv, including its small size, ease of modification, and ability to be engineered for enhanced affinity and specificity, are also described. Finally, such challenges as immunogenicity, stability, and scalability, alongside strategies to overcome these hurdles, are deeply scrutinized to provide safer and more effective strategies for the diagnosis and treatment of the incurable CVDs.